Application of the Numerical-Analytic Method to Systems of Differential Equations with Parameter - Yanovskii, L. P. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
The numerical-analytic method is applied to systems of differential equations with parameter under the assumption that the corresponding functions satisfy the Lipschitz conditions in matrix notation. We also obtain several existence results for problems with deviations of an argument.